ANALISIS PENGARUH PENGALAMAN AUDIT, BEBAN KERJA, SKEPTISME PROFESIONAL, DAN INDEPENDENSI TERHADAP KEMAMPUAN AUDITOR MENDETEKSI FRAUD - Dewi Saptantinah Puji Astuti, Kristian Fernando Irawan, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This study tested the influence of audit experience, workload, skepticism, and professional independence against the ability of Auditors to detect fraud. This study used a survey of studies on public accounting Auditors on the city of Surakarta and Yogyakarta. The data type used is qualitative data and quantitative data, the source data used the primary data. The population in this research is the auditor who worked in public accounting in the region of Surakarta and Yogyakarta as much as 133 respondents. The sample in this research are all members of the population taken as a sample of the research, based on the number of questionnaires returned. The research sample is determined by random sampling techniques. Technique of data analysis used a classic assumption test, and multiple linear regression analysis. The results of the analysis of the data shows that: (1) auditing experience a positive effect against the ability of Auditors to detect fraud, (2) the negative effect of the workload against the ability of Auditors to detect fraud, (3) positive influential professional skepticism against the ability of Auditors to detect fraud, (4) a positive effect against the independence of the auditor's ability to detect fraud.Keywords: fraud, audit experience, workload, skepticism, independence.